2018
DOI: 10.29196/jubpas.v26i10.1848
|View full text |Cite
|
Sign up to set email alerts
|

The Using of PCA, Wavelet and GLCM In Face Recognition System, A Comparative Study

Abstract: The process of data dimension reduction plays an important role in any  face recognition system because many of these data are repetitive and irrelevant and this cause a problem in applications of data mining and learning the machine. The main purpose is to improve the performance of recognition by eliminating repetitive features.           In this research, a number of data reduction techniques were used like: Principal Component Analysis, Gray-Level Co-occurrence Matrix and Discrete Wavelet Transform f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Here the experiment was conducted on ORL and AR face databases. Al-Abaji and Salih [20] were proposed one-dimensional data reduction techniques namely, GLCM, PCA, DWT with Euclidian distance classifier for face recognition. In this work, the PCA features, HH segment band DWT features, and the GLCM of energy, contrast, correlation, and homogeneity features were considered for the experiment.…”
Section: Related Workmentioning
confidence: 99%
“…Here the experiment was conducted on ORL and AR face databases. Al-Abaji and Salih [20] were proposed one-dimensional data reduction techniques namely, GLCM, PCA, DWT with Euclidian distance classifier for face recognition. In this work, the PCA features, HH segment band DWT features, and the GLCM of energy, contrast, correlation, and homogeneity features were considered for the experiment.…”
Section: Related Workmentioning
confidence: 99%
“…Among the most popular statistical methods used to extract texture characteristics is the co-occurrence matrix and obtaining a number of traits based on mathematical equations in which the intensity distribution and relative placements of nearby pixels in an image are described [10], [11]. In this paper, four traits will be used as in the following equations:…”
Section: Co-occurrence Matrixmentioning
confidence: 99%
“…The study showed the third level is the best level of disassembly [14]. In the other work [15], a descriptor is obtained by projecting a face as an input on a eigenface space, then the descriptor is fed as an input to each object's pre-trained network. They determine and report the maximum output if it passes the threshold previously established for the recognition system.…”
Section: Related Workmentioning
confidence: 99%